Utilizing innovative technologies to address the public health impact of climate change emerging research and opportunities - Weiss-Randall, Debra (Advances in environmental engineering and green technologies (AEEGT) book series, 2018)
This book presents an overview of global warming and greenhouse gas emissions, key indicators of climate change, regional trends in the United States, and global trends and impacts, explores the major health impacts of climate change, and their impact on vulnerable populations, explores climate change and environmental justice, describes the DOI Framework, and other topics.